Experimental investigations on mechanical behavior of the carbon fiber tube reinforced polyurethane foam. (October 2020) - Zhang, Yong; Yan, Xiaogang; Huang, Wenzhen; Lin, Jiming
Abstract: The paper proposes a carbon fiber tube reinforced polyurethane foam material (CPM). Mechanical behavior of the CPM is investigated by quasi static crushing experiment. The results show that the carbon fiber tube reinforced design can obviously improve the energy absorption and load carrying capacity of the polyurethane (PU) foam. Parameter studies show that the density of the PU foam, the number and the diameter of the thin carbon fiber tube have significant effect on mechanical performance of the CPM. Moreover, the CPM filled thin walled columns (aluminum column or carbon fiber column) are further developed and their crushing behaviors are investigated under axial crushing conditions. The results show that the CPM filled design can effectively improve the crashworthiness of the aluminum column or the carbon fiber column. The interaction behavior between the CPM and the thin-walled column presents a significant contribution to energy absorption of the CPM filled columns. Moreover, the CPM filled carbon fiber column has greater potential to improve the crashworthiness than the CPM filled aluminum column. The research findings of this paper provide a new method for designing the lightweight protective structure. Highlights: The paper proposes a new carbon fiber tube reinforced polyurethane material (CPM). The CPM enhances the energy absorption and load uniformity of the polyurethane (PU) foam. The number and diameter of the CFRP tube have significant effect on the energy absorption. The CPM filled column can improve the mechanical performance of the single wall column. The CPM is an effective way to design a new lightweight protective structure.